2019
DOI: 10.1021/acs.iecr.8b04888
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic or Hydrophilic Porous Metallic/Ceramic Tubular Membranes for Continuous Separations of Biodiesel–Water W/O and O/W Emulsions

Abstract: This paper reports the effective surface effect of porous inorganic membranes on improving the emulsion separations (i.e., perm-selective extraction of either oil phase or aqueous phase from the emulsions). A novel tubular form of superwetting, porous, stainless steel/ceramic membranes were demonstrated for enabling continuous separations of oil–water emulsions, extracting either oil phase or aqueous phase from the flowing emulsions. The superhydrophobic membranes consist of macroporous (4 μm) stainless-steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
(18 reference statements)
1
13
0
Order By: Relevance
“…Varanasi et al showed rare-earth oxide ceramics materials promoted dropwise condensation, repelling water droplets and sustaining hydrophobicity even after exposure to harsh environments [55]. Other ceramic membranes grafted and coated by perfluorosilane showed promising results [56][57][58][59]. In condensate condition, self-cleaning of superhydrophobic surfaces by self-propelled droplet jumping and sweeping have also been demonstrated by several studies [30,32,[60][61][62].…”
Section: Introductionmentioning
confidence: 92%
“…Varanasi et al showed rare-earth oxide ceramics materials promoted dropwise condensation, repelling water droplets and sustaining hydrophobicity even after exposure to harsh environments [55]. Other ceramic membranes grafted and coated by perfluorosilane showed promising results [56][57][58][59]. In condensate condition, self-cleaning of superhydrophobic surfaces by self-propelled droplet jumping and sweeping have also been demonstrated by several studies [30,32,[60][61][62].…”
Section: Introductionmentioning
confidence: 92%
“…Membrane separation processes can be classified into four categories according to the pore size: microfiltration, ultrafiltration, nanofiltration, and reverse osmosis [ 24 , 25 , 26 ]. The pore size of the membrane determines the filtration properties of water/oil emulsions, which can also vary, depending on the concentration of the oil in the emulsion and, consequently, on the size of the oil drop [ 13 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…[16] By retrieving the kinds of literatures in this field, [17][18][19][20][21] it was found that the materials in the form of the membrane were promising for the separation of different emulsions, especially those with hierarchical structures consisting of fibre and nanoparticles/features, such as stainless steel mesh coated with ZnO nanowires, [22] cotton fibres with roughened morphology in nano-scale, [23] ceramic membrane coated with Al 2 O 3 nanoparticles. [24] While much progress has been made in this field, restrictive factors like the cost, availability of raw materials as well as complicated preparation process, were remained more or less for the scaleup production of the material.…”
Section: Introductionmentioning
confidence: 99%